Perbandingan Kinerja Tenaga Penjual Sebelum dan Setelah Menggunakan PDA (Personal Digital Assistant) Pada PT. Bentoel Prima Asmo (Area Sales & Marketting Officer) Bogor - M. Nur Rizqi; Muhammad Ramdhany (STIE Binaniaga, 2009)
Cigarette industry in Indonesia is an industry that absorbs a lot of manpower/human resources (HR). HR needs ranging from planting tobacco and clove plantations, drying tobacco and cloves, chopped pelintingan tobacco and cigarattes in the factories to street vendors who sell cigarettes on the streets. Cigarette industry in Indonesia, employing about 500.000 employees, who work directly on the plant and at all levels of organizational structure (Siska ,2004). It often happens to overlap tasks to complete a series of activities to produce an output. Linkage of a job, sections, departments, divisions within an organization is a narulal thing, but the need for regulating the organization in order to avoid miscommunication, a prolonged conflict between functions or even let go of responsibilities, which can ultimately result in descreased performance of the organization it self (Dessler, 1998). The result of research conducted with two different test average of salesperson performance comparison before and after the use of PDAs by using independent sample test. This is demonstrated by the results obtained pengujan where the average value 3.42 before the use of PDAs and PDA after the use-value 3.91. Standard deviation value 0.49 before the use of PDAs and PDA after the use-value 0.55, which means greater than 0.00. Salesperson performance in sales volume before and after use of a PDA in PT. Bentoel Prima Bogor ASD are real or significant.